Meta Analisis E-Book dan Edupark Terhadap Landasan Pendidikan Pada Pembelajaran Revolusi Industri 4.0 - Sadraini, Sadraini; Rifai, Hamdi (Jurnal Penelitian Pembelajaran Fisika, 2019)
The 21st century challenge of the industrial revolution 4.0 is implementing learning resources in the 2013 curriculum that can be integrated with regional contexts that can support digital-based learning. Physics Learning Integrating Learning Materials with the Environment and Physics Learning Applications becomes More Interesting. Various kinds of learning resources that can be integrated in learning physics with the environment or educational park (Edupark). Edupark is an educational park to support the application of physics concepts for students. Meanwhile, the 4.0 industrial revolution era brought education based on digital learning. Digital learning such as e-books are integrated with Edupark. The foundation of education greatly contributes to specific learning in achieving the learning objectives achieved. So, a meta-analysis of e-books and eduparchs of physics was carried out on the educational foundation of the industrial revolution era 4.0. This meta analysis uses descriptive methods. The purpose of the meta-analysis is to select 20 educational journals in the selected journals. The data in this study were obtained from the analysis of each journal and obtained with existing theories. The technique of analyzing data uses descriptive percentages. The results of the meta-analysis concluded that the application of religious foundations with a percentage of 5% (Not good), constitutional basis 60% (enough), philosophical foundation 85% (Good), social, cultural and anthropological foundation 45% (not good), and the application of science and technology 75% (enough).